2022
DOI: 10.1002/csc2.20750
|View full text |Cite
|
Sign up to set email alerts
|

Is seed coat structure at fault for altered permeability and imbibition injury in artificially aged soybean seeds?

Abstract: Ageing induces many deteriorative changes to seeds during storage like genetic damage, protein degradation, enzyme inactivation and loss of membrane integrity. In this study, we subject to investigate the alterations in seed coat structure and its permeability properties due to accelerated ageing affecting the subsequent imbibition of soybean [Glycine max (L.) Merr.] seeds. Two contrasting seed coat colour genotypes, JS 335 (white) and Bhatt (black) were selected and artificially aged for 48 and 72 h. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 52 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The seeds' good physical quality illustrates the minimal damage that genetic material from wild plants can present, allowing for a quick and easy determination of their germination potential. Generally, seed damage can occur during fruit harvesting or the seed aging process during storage (Satya Srii et al, 2022). Here, we demonstrated that the collected chiltepín pepper seeds had minimal to no physical damage to the pericarp.…”
Section: Discussion Discussion Discussionmentioning
confidence: 60%
“…The seeds' good physical quality illustrates the minimal damage that genetic material from wild plants can present, allowing for a quick and easy determination of their germination potential. Generally, seed damage can occur during fruit harvesting or the seed aging process during storage (Satya Srii et al, 2022). Here, we demonstrated that the collected chiltepín pepper seeds had minimal to no physical damage to the pericarp.…”
Section: Discussion Discussion Discussionmentioning
confidence: 60%
“…Seed imbibition used an electronic balance (ESSAE; FB 200‐172‐14666; Integral Industrial Services Private Limited, Noida, India) approach, by measuring weight differences as described in Satya Srii et al . (2022). Three replicates of 10 seeds of each genotype were used.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study on soybean seeds (Satya Srii et al . 2022) found that white seed coats of JS 335 were more prone to imbibitional injury than black seed coats of Bhatt due to differences in permeability related to variations in seed coat structure. However, this work did not explore the difference in seed coat chemical composition between the two genotypes that might influence seed coat permeability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations